2009
DOI: 10.1128/jvi.02188-08
|View full text |Cite
|
Sign up to set email alerts
|

NS5 of Dengue Virus Mediates STAT2 Binding and Degradation

Abstract: The mammalian interferon (IFN) signaling pathway is a primary component of the innate antiviral response. As such, viral pathogens have devised multiple mechanisms to antagonize this pathway and thus facilitate infection. Dengue virus (DENV) encodes several proteins (NS2a, NS4a, and NS4b) that have been shown individually to inhibit the IFN response. In addition, DENV infection results in reduced levels of expression of STAT2, which is required for IFN signaling (M. Jones, A. Davidson, L. Hibbert, P. Gruenwald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
466
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(485 citation statements)
references
References 55 publications
17
466
1
1
Order By: Relevance
“…Gene expression studies indicated that STAT2 overexpression is not driving antiviral signaling like IRF1. Previous studies have shown that the DENV NS5 polymerase potently antagonizes IFN signaling by mediating STAT2 degradation (35,36). Our data fit this mechanism and suggest that STAT2 overexpression may be sufficient to squelch DENV replication by stoichiometrically overcoming the viral NS5 polymerase.…”
Section: Resultssupporting
confidence: 72%
“…Gene expression studies indicated that STAT2 overexpression is not driving antiviral signaling like IRF1. Previous studies have shown that the DENV NS5 polymerase potently antagonizes IFN signaling by mediating STAT2 degradation (35,36). Our data fit this mechanism and suggest that STAT2 overexpression may be sufficient to squelch DENV replication by stoichiometrically overcoming the viral NS5 polymerase.…”
Section: Resultssupporting
confidence: 72%
“…1A, supplemental Table S5). Of the 20 DENV-human protein interactions identified in the literature, only the interaction between NS5 and STAT2 was also detected in this study (85,86). Other proteins in our data set (UBE2I, CALR, and PTBP1) were reported to interact with DENV proteins, though the interacting viral proteins differ from those identified here (87)(88)(89)(90)(91); these host factors may bind to multiple DENV proteins, as has previously been observed for other viruses (21), or may represent false-positives.…”
Section: Mapping the Denv-human Protein Interactioncontrasting
confidence: 44%
“…NS5 recruits at least NS3 and a subset of host cellular proteins to form the replication complex or 'replicase' in virus-induced membranous compartments for productive viral RNA synthesis (Bidet & Garcia-Blanco, 2014). NS5 also plays important roles as an immune suppressor by downregulating type I IFN responses through interacting with STAT2 (Ashour et al, 2009). Moreover, both NS3 and NS5 were implicated in DHF as they were found to be the immunodominant T-cell antigens compared to other viral proteins (Duangchinda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%